Eksperimen Pembelajaran Matematika Dengan Strategi Students Teams Achievement Division (STAD) Dan Think Pair Share (TPS) Ditinjau Dari Kemampuan Awal Siswa Kelas Xi Ips Semester 2 Di Sman 2 SukoharjoTahun 2015/2016 - Purwaningrum, Dewi; Dr. Sumardi, Dr. Sumard.i,M.Si (2016)
experiment with Students Teams Achievement Division (STAD) and Think Pair Share (TPS) strategy in term of the early math ability of the students of grade XI IPS semester two in state Senior High School two of Sukoharjo School Year of 2015/2016. Thesis, Surakarta: Master of Educational Administration Postgraduate School, Muhammadiyah University of Surakarta.July, 2016. Learning outcomes required to determine the achievement of competence given after the learning process as a form of evaluation in education.This research aims to test : (1) The effect of STAD learning strategy and TPS learning strategy on learning outcomes in mathematics, (2) The effect of early math abilities on learning outcomes in mathematics, (3) interaction between learning strategy and early math abilities on learning outcomes in mathematics. The type of research is quantitative approach with quasi experimental design. The population of this research were students of XI grade with IPS department at SMAN 2 Sukoharjo in 2015/2016 academic year. The research samples are XI IPS 1 as a experiments class using STAD learning strategy and XI IPS 3 as a control class using TPS learning strategy. Samples taken by cluster random sampling.Data collection method used is the test and documentation. The analysis technique used is two-way analysis of variance test different cells, previously performed using methods normality test and homogeneity test. Based on the research result with =5%, (1) learning outcomes in mathematics with STAD is better than TPS sothere are effect of STAD learning strategy and TPS learning strategy on learning outcomes in mathematics; (2) learning outcomes in mathematics with high early math abilities categories is better than medium ang low early math abilities, so there are effect of early math abilities on learning outcomes in mathematics; (3) On STAD strategies, students who have high early math abilities categories get learning outcomes is better than students with medium and low early math abilities categories.Similarly on the application of TPS strategies. So there are interaction between learning strategy and early math abilities on learning outcomes in mathematics. Keywords :early math abilities, learning outcomes in mathematics, STAD, TPS